Comparative study of the use of online reading strategies in the L1 and L2 - Habók, Anita; Oo, Tun Zaw; Magyar, Andrea (Frontiers in Education, 2025)
IntroductionOnline reading skills are essential for learning English. Thus, this article aims to examine the relation between online reading strategies used in the native language (L1) and English as a foreign language (L2) among young Hungarian readers.MethodsUsing the Online Survey of Reading Strategies (OSORS) questionnaire, data were collected from 1,214 lower secondary school students. The measures for construct validity and differential item functioning via Rasch analysis demonstrate that the instruments were reliable and valid.Results and discussionThe results show that the students most frequently used global reading strategies in the L1 and support-reading strategies in the L2. Using R programming, correlation analysis finds no significance in students' reading strategy use between their L1 and L2, although the study notes the significant positive impacts of the three reading strategies on their L1 and L2. Through multivariate analysis of variance, the study proposes that there exists a moderate relation between students' attitudes toward language and their use of online reading strategies. Lastly, regression analyses using MPlus8 illustrate that global and support reading strategies had positive and significant effects on the students' reading comprehension achievement. Therefore, the results could be beneficial to language teachers and students.